2018
DOI: 10.3390/ijerph15040744
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment on Hazardous Ingredients in Household Deodorizing Products

Abstract: The inhalation of a water aerosol from a humidifier containing disinfectants has led to serious lung injuries in Korea. To promote the safe use of products, the Korean government enacted regulations on the chemicals in various consumer products that could have adverse health effects. Given the concern over the potential health risks associated with the hazardous ingredients in deodorizing consumer products, 17 ingredients were analyzed and assessed according to their health risk on 3 groups by the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results from the AENET analysis highlight the value of variable selection techniques in studies of correlated exposure biomarkers. We observed that dichlorophenol biomarkers in particular were correlated with the urinary phthalate metabolites MBzP, MBP, and MiBP, which may be attributable to shared exposure sources including pharmaceuticals, cleaning products, and deodorizers ( Hauser et al, 2004 ; Lee et al, 2018 ; Ye et al, 2014 ). Among the phthalate metabolites measured, these compounds showed the strongest associations with urinary oxidative stress biomarkers in our previous work ( Ferguson et al, 2014a ).…”
Section: Discussionmentioning
confidence: 88%
“…The results from the AENET analysis highlight the value of variable selection techniques in studies of correlated exposure biomarkers. We observed that dichlorophenol biomarkers in particular were correlated with the urinary phthalate metabolites MBzP, MBP, and MiBP, which may be attributable to shared exposure sources including pharmaceuticals, cleaning products, and deodorizers ( Hauser et al, 2004 ; Lee et al, 2018 ; Ye et al, 2014 ). Among the phthalate metabolites measured, these compounds showed the strongest associations with urinary oxidative stress biomarkers in our previous work ( Ferguson et al, 2014a ).…”
Section: Discussionmentioning
confidence: 88%
“…Because ice cubes produced are delivered directly to the consumer in the final product without further sterilizing procedures, the risk for microbial exposure may be increased. Because public interest in chemicals is increasing because of humidifier sanitizer accidents (Lee et al, ), an acceptable range of chemical constituents in food grade tools was recently established, but the availability of cleaning or disinfection regarding microbial safety was not addressed. These factors are not legally considered when approving the import or production of food machinery.…”
Section: Resultsmentioning
confidence: 99%